(untitled) (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
This study aims to analyze the influence of price and product design on the purchase decision of e-marketplace fashion products with brand image mediation in Bali Province. This study obtained 200 valid samples. This study used PLS-based SEM as an analytical tool. The results showed that price, product design, and brand image have a positive and significant influence on brand image and purchase decision. Brand image mediates the influence of price and product design on purchase decision. Aspects that need to be considered to increase purchase intention through prices are ensuring prices are affordable by the target market, prices in accordance with product quality, competitive prices with similar competitors’ offers, prices following the benefits obtained by consumers, and providing regular discounts. In the product design aspect, namely up-to-date clothing models, varied product design choices, materials with long durability, comfortable products to wear, and stylish. In brand image, marketers need to ensure the brand is known to consumers, has a good reputation, and builds a good emotional connection with consumers.